Lippincott's textbook for long-term care nursing assisstant : a humanistic approach to caregiving - Carter, Pamela J.; Goldschmidt, Wanda M. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2010)
Focuses on preparing nursing assistants to work in the long-term care setting (that is, nursing homes and assisted-living facilities). This book helps the students to understand the long-term care environment, which is heavily regulated by the government